Report of the first international workshop on onchocerciasis-associated epilepsy - Robert Colebunders; Michel Mandro; Alfred K. Njamnshi; Michel Boussinesq; An Hotterbeekx; Joseph Kamgno; Sarah O’Neill; Adrian Hopkins; Patrick Suykerbuyk; Maria-Gloria Basáñez; Rory J. Post; Belén Pedrique; et al. (Infectious Diseases of Poverty, 2018)
Abstract Background Recently, several epidemiological studies performed in Onchocerca volvulus-endemic regions have suggested that onchocerciasis-associated epilepsy (OAE) may constitute an important but neglected public health problem in many countries where onchocerciasis is still endemic. Main text On October 12–14th 2017, the first international workshop on onchocerciasis-associated epilepsy (OAE) was held in Antwerp, Belgium. The workshop was attended by 79 participants from 20 different countries. Recent research findings strongly suggest that O. volvulus is an important contributor to epilepsy, particularly in meso- and hyperendemic areas for onchocerciasis. Infection with O. volvulus is associated with a spectrum of epileptic seizures, mainly generalised tonic-clonic seizures but also atonic neck seizures (nodding), and stunted growth. OAE is characterised by an onset of seizures between the ages of 3–18 years. Multidisciplinary working groups discussed topics such as how to 1) strengthen the evidence for an association between onchocerciasis and epilepsy, 2) determine the burden of disease caused by OAE, 3) prevent OAE, 4) improve the treatment/care for persons with OAE and affected families, 5) identify the pathophysiological mechanism of OAE, and 6) deal with misconceptions, stigma, discrimination and gender violence associated with OAE. An OAE Alliance was created to increase awareness about OAE and its public health importance, stimulate research and disseminate research findings, and create partnerships between OAE researchers, communities, advocacy groups, ministries of health, non-governmental organisations, the pharmaceutical industry and funding organizations. Conclusions Although the exact pathophysiological mechanism underlying OAE remains unknown, there is increasing evidence that by controlling and eliminating onchocerciasis, OAE will also disappear. Therefore, OAE constitutes an additional argument for strengthening onchocerciasis elimination efforts. Given the high numbers of people with epilepsy in O. volvulus-endemic regions, more advocacy is urgently needed to provide anti-epileptic treatment to improve the quality of life of these individuals and their families.